The lion, the witch, and the wardrobe - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 1994)
Four English school children find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch who has cursed the land with eternal winter.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.5
5-8
Keywords: Children -- Fiction; Fantasy; Good and evil -- Fiction; Narnia (Imaginary place) -- Fiction; Children -- Fiction; Good and evil -- Fiction; Narnia (Imaginary place) -- Fiction; Fantastic fiction